Implementation of Environmental Health Services (Sanitation Clinic) in Public Health Centers Indonesia - Intan Sekar Arumdani; Indah Sekar Arumdani; Alifia Intan Berlian (Universitas Diponegoro, 2021)
The Indonesian government has implemented clinical sanitation to improve a healthier environment and reduce mortality from environmental-based diseases. This effort is carried out to reduce the incidence of environmental-based diseases such as diarrhea and Acute Respiratory Infections (ARI). However, in 2017 the number of ARI sufferers in one of the provinces in Indonesia reached 45.38%, while diarrhea reached 28.3%. The diarrhea mortality rate increased to 4.76% in 2018, while the prevalence of ARI reached 9.1%. Therefore, this article aims to examine the performance of the sanitation clinic program at the Indonesian Health Center. The review method used is the narrative. Total percentage of 78.33% for the category of public health centers that have carried out the stages of sanitation clinics starting from the counselling stage to the intervention stage following established regulations. This percentage is still low because it has not received a 100% score. The implementation of the program has not been supported by adequate counselling media. In addition, the Public Health Center does not yet have a counselling room, and there is still a shortage of operational funds. Monitoring and evaluation need to be carried out to improve the service performance of the sanitation clinic program.